Tourism development: a geographical perspectives - Awang, Khairil Wahidin; Wan Hassan, Wan Melissa; Mohd Zahari, Mohd Salehuddin (Canadian Center of Science and Education, 2009)
This paper represents an effort to conceptualise tourism and development, and their interlinking features, within the broad geographical perspective. It suggests that, as an industry, tourism has evolved along the development path of dominant development theories; Modernisation, Dependency, Neo-liberalism and Alternative development. The findings suggest that, by utilising the frameworks of these development theories, one could analyse and evaluate dynamic tourism processes, a necessity in understanding how tourism works.